Пути развития отрасли свиноводства и повышение конкурентоспособности ее продукции - Болтянская, Наталья Ивановна; Болтянська, Наталя Іванівна; Boltianska, Natalia (My University, 2012)
RU: Рассмотрены пути развития отрасли свиноводства и повышение конкурентоспособности ее продукции. EN: The ways of development of indus-try of the pig breeding are analysed and the row of basic principles the observance of which at planning provides the maximally effective pro-duction of pork is certain.
Рaths of development of branch of swine breeding and raise competitive strength of its products
Keywords: свиноводство; животноводство; система гибридизации; смешанные корма; механизация и автоматизация производственного процесса; отклонения от норм технологического проектирования; самосплавные системы навоза; транспортерные механические системы; теплоутилизаторы разных типов; энергозатраты; рig breeding; plant-breeding-genetic centers; system of hybridization; mixed fodders; mechanizations and automation of production processes